APPLICATION OF US-EPA METHOD 29: SAMPLING OF METALS EMISSIONS FROM STATIONARY SOURCE - Kardono, Kardono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
This report summaries the results of sampling (and analyses) of stack flue gas of P.T. Semen Cibinong’s Kiln, located at Jl. Raya Narogong, Desa Nambo, Cileungsi, Bogor. The test was aimed to determine concentrations of emitted metals (As, Cd, Cr, Pb, Hg and Tl) concentrations. The conditions of the kiln tested were maintained at its normal operation. The metals were sampled from the flue gas at 3 (three) replicates. The metals concentrations in all three tests were well below the standard as stipulated in Kep-06/BAPEDAL/02/1999. This stack sampling work was carried out with the strict procedures specified by United States Environmental Protection Agency (US-EPA), Method No. 29. The laboratory analysis of metals were conducted by Analitika Sejahtera Lingkungan (ASL) laboratory, Bogor. The procedures of both stack sampling and laboratory analyses have followed a quality assurance/ quality control (QA/QC) program as an integral part of the overall technical effort.